The Applied Artificial Intelligence Workshop Start working with AI today, to build games, design decision trees, and train your own machine learning models - So, Anthony (Packt Publishing Limited, 2020)
bWith knowledge and information shared by experts, take your first steps towards creating scalable AI algorithms and solutions in Python, through practical exercises and engaging activities/b h4Key Features/h4 ulliLearn about AI and ML algorithms from the perspective of a seasoned data scientist /li liGet practical experience in ML algorithms, such as regression, tree algorithms, clustering, and more /li liDesign neural networks that emulate the human brain/li/ul h4Book Description/h4 You already know that artificial intelligence (AI) and machine learning (ML) are present in many of the tools you use in your daily routine. But do you want to be able to create your own AI and ML models and develop your skills in these domains to kickstart your AI career? The Applied Artificial Intelligence Workshop gets you started with applying AI with the help of practical exercises and useful examples, all put together cleverly to help you gain the skills to transform your career.